A third species of the rare frog genus Holoaden (Terrarana, Strabomantidae) from a montane rainforest area of southeastern Brazil - Pombal Jr., José P.; Siqueira, Carla C.; Dorigo, Thiago A.; Vrcibradic, Davor; Rocha, Carlos Frederico D. (Zootaxa, 2008)
A new species of the rare anuran genus Holoaden is described from a montane rainforest area in Rio de Janeiro State, southeastern Brazil. The new species is characterized by its large body size, large head, moderately bulging dorsal glands, limbs long and slender, a deeply dark dorsal coloration, and dark ventral surface with a light abdominal blotch of variable size. The new species expands the range of the genus 200 km eastward in Brazil.